1998
DOI: 10.1038/jidsymp.1998.25
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Detergent-Induced Barrier Alterations — Effect of Barrier Cream on Irritation

Abstract: To gain a better understanding of the interaction of the model detergent sodium lauryl sulfate (SLS) with the stratum corneum, we investigated systematically the ultrastructural changes of the epidermal barrier and the nucleated parts of the epidermis after the occluded application of different concentrations of SLS in human. Different application models were investigated. Two of the three irritation procedures (long duration exposure and the repetitive exposure for 3 d) provoked damage of the nucleated parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
86
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 0 publications
4
86
1
5
Order By: Relevance
“…These findings are in accordance with those reported by Fartasch et al [22,23], who demonstrated a similar behavior in the interaction of sodium dodecyl sulfate surfactant (SDS) with human SC. In line with our results, these authors demonstrated by transmission electron microscopy with OsO 4 and RuO 4 staining that SDS causes mainly dam- ages in the epidermis cells and in the SC corneocyte envelopes.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are in accordance with those reported by Fartasch et al [22,23], who demonstrated a similar behavior in the interaction of sodium dodecyl sulfate surfactant (SDS) with human SC. In line with our results, these authors demonstrated by transmission electron microscopy with OsO 4 and RuO 4 staining that SDS causes mainly dam- ages in the epidermis cells and in the SC corneocyte envelopes.…”
Section: Resultssupporting
confidence: 83%
“…Although this loss of order in the lipid structure could be the main cause of the loss of SC cohesion, the results obtained in the SC extracted with organic solvents (preservation of the cohesion but removal of the lamellar lipid structure) do not seem to support this hypothesis. Considering the present results and those reported in earlier studies about the general irritant effect of surfactant on SC in vivo [8,[22][23][24], it can be assumed that this irritant response could be associated with the disruption of the corneocyte and the corneocyte envelope. In this sense, the reinforcement or protection of these structures could reduce or even prevent this harmful effect.…”
Section: Resultsmentioning
confidence: 66%
“…It is well known that treatment with surfactants perturbs the skin barrier due to the depletion of intercellular lipids in the stratum corneum [8, 9, 18, 29]. To precisely determine the effects of Cer as major intercellular components on barrier homeostasis associated with surfactant treatment and to distinguish them from an occlusive effect (such as seen with Vaseline), we examined the repairing effects of the topical application of PACer on SDS-induced barrier perturbation.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 39 controlled trials (table 1) investigating the effect of BCs against skin irritants in a total of 929 volunteers (172 men, 279 women and 481 unspecified subjects) with healthy skin (n = 28), hand dermatitis (n = 1), skin sensitized to a specific allergen (n = 4) and 1 study on latex glove allergens [6,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. From these 39 papers, studies on excised skin [18,24,40,41,43,46] have been discarded, and only trials on subjects with healthy and non-sensitized skin were retained, reducing the list to 27 papers detailed in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The contact time of irritants ranges from 5 s to 24 h but the most frequent contact time is 30 min (n = 11) and 24 h (n = 4). Repetitive irritation tests, including repetitive occlusive irritation tests and tandem repetitive irritation tests, were performed in 11 studies [22,23,26,30,31,32,36,38,42,44,50]. The assessment methods often consist of clinical scoring of irritation after cutaneous patch tests (n = 17) and bioengineering methods which are habitually evaporimetry (n = 17), colorimetry (n = 12), corneometry (n = 7), flow velocimetry by Doppler laser (n = 6), spectrometry (n = 3) or other more infrequently used methods.…”
Section: Resultsmentioning
confidence: 99%